Cardiac fibrosis: emerging agents in preclinical and clinical development. (1st February 2021) - Spoladore, Roberto; Falasconi, Giulio; Fiore, Giorgio; Di Maio, Silvana; Preda, Alberto; Slavich, Massimo; Margonato, Alberto; Fragasso, Gabriele
ABSTRACT: Introduction: Myocardial fibrosis is a remarkably dynamic process mediated by different molecular pathways that represent potential targets of novel therapeutic interventions. Transforming Growth Factor-beta (TGF-β), connective Tissue Growth Factor (cTGF) and Galectin-3 (Gal-3) represent the most promising targets on which research has been currently focusing. Area Covered: This review initially discusses those drugs used in clinical practice for their anti-fibrotic properties and later examines emerging pathway-specific agents in preclinical and clinical development [phase I and II-concluded or ongoing trials]. We performed a PubMed, Embase and Google Scholar research including original articles, systematic reviews, ongoing and completed trials using combinations of keywords such as 'myocardial fibrosis', 'reverse remodeling', 'RAAs', 'therapy'. Expert Opinion: A variety of preclinical evidences suggest that new drugs and molecules are potentially useful to target cardiac fibrosis and improve left ventricular function, reduce infarct size and scars, delay incident heart failure and cardiac dysfunction in animal models. However, there are very few clinical trials investigating the effect of such drugs in this setting, as well as a lack of new engineered molecules for specific targets.